Advanced Education Based on Effective Learning Book Guide Motivative to Improve Ability to Write Short Storie - Erlita Erlita; Sam Hermansyah; Roni Roni (Edumaspul: Jurnal Pendidikan, 2024)
This research focused on entrepreneurship education-based learning within motivation guidebook. The purpose of the research was to determine the effectiveness of the entrepreneurship education-based learning within motivation guidebook on students ' short stories writing skills. This research was a quantitative type of research. It was conducted to students of grade XI in SMA Negeri 6 Sidrap. Data collection method was a short stories writing test. Data analysis was conducted by t-test formula to determine whether there was an improvement before and after the treatment. The results of the research indicated that value of t count was 6.62 and on 5% significance, n = 30, t table = 1.68. The t count was higher than t table , meaning that Ha was acceptable. Thus, the learning of entrepreneurship education-based short story writing within motivation guidebook was effective to develop short story writing skills.